Development of a Guided Inquiry-Scientific Laboratory (GISL) Based Health Chemistry Practicum Module - Nafillah, Khoirotun (Universitas Islam Indonesia, 2024)
Chemistry practicum learning requires a comprehensive approach, which improves understanding of concepts and develops various essential skills needed in the professional and academic world. This research aims to develop a Guided Inquiry-Scientific Laboratory-based Health Chemistry module and conduct empirical feasibility tests. This module is designed with a guided inquiry approach integrated with scientific methods in laboratory activities. The practicum module was developed for second-grade vocational school students in health expertise with material covering colloids, hydrocarbons, polymers, biomolecules, and chemical separation. This development research uses the Borg and Gall model, which consists of planning, organizing, implementing, assessing, and analyzing data. This research was only carried out to the validation stage by material experts, media experts, peer reviewers, and reviewers (five Health Vocational School teachers). The assessment carried out by the reviewer includes eight assessment aspects with 30 assessment indicators. Data was collected through questionnaires, observations, and interviews. Data analysis was carried out descriptively, quantitatively, and qualitatively, guided by ideal assessment criteria to determine the quality of the practicum module. The research results show that the Guided Inquiry-Scientific Laboratory (GISL) based Health Chemistry practicum module that has been developed has a score of 132.52 with an ideal percentage of 88.3467% in the very good (SB) category. This indicates that this module is suitable for use in health chemistry practicum learning, and it is hoped that this research can be continued at the next stage.